2001
DOI: 10.1074/jbc.m102641200
|View full text |Cite
|
Sign up to set email alerts
|

Cbl-b-dependent Coordinated Degradation of the Epidermal Growth Factor Receptor Signaling Complex

Abstract: The Cbl proteins are a family of proteins found in metazoans from nematodes to vertebrates. These proteins have several highly conserved domains including an N-terminal tyrosine kinase binding (TKB) 1 domain and a RING finger (1-9). The three mammalian Cbl proteins,2,[6][7][8], are tyrosine-phosphorylated upon activation of a wide variety of growth factor receptors, and they associate with many signaling proteins via SH2 and SH3 interactions (reviewed in Ref. 10 and 11). These diverse interactions modulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(165 citation statements)
references
References 58 publications
11
150
2
1
Order By: Relevance
“…Previous work has shown that Cbl is recruited to the autophosphorylated Y323 of Syk (Lupher et al, 1998) and that Cbl is targeted by the Nedd4/AIP4 family of E3 ubiquitin ligases (Magnifico et al, 2003). The regulation of CblC by AIP4 is an important part of the mechanism for downregulation of the epidermal growth factor receptor signaling complex (Ettenberg et al, 2001;Courbard et al, 2002). The interactions of Cbl with Syk and AIP4 may explain why we detect Cbl in immunoprecipitates of LMP2A (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Previous work has shown that Cbl is recruited to the autophosphorylated Y323 of Syk (Lupher et al, 1998) and that Cbl is targeted by the Nedd4/AIP4 family of E3 ubiquitin ligases (Magnifico et al, 2003). The regulation of CblC by AIP4 is an important part of the mechanism for downregulation of the epidermal growth factor receptor signaling complex (Ettenberg et al, 2001;Courbard et al, 2002). The interactions of Cbl with Syk and AIP4 may explain why we detect Cbl in immunoprecipitates of LMP2A (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…The overexpression of Cbl proteins enhances EGF-induced ubiquitination and downregulation of the WT EGFR (Ettenberg et al, 1999b(Ettenberg et al, , 2001Levkowitz et al, 1999;Waterman et al, 1999b;Yokouchi et al, 1999). Therefore, we investigated whether the Cbl proteins also regulate the constitutively active mutant EGFRvIII in a cell line Chinese hamster ovary (CHO) that does not express the WT EGFR.…”
Section: Cbl Proteins Ubiquitinate and Downregulate The Constitutivelmentioning
confidence: 99%
“…In contrast, the deletion of the TKB domain containing the aminoterminus of Cbl-b (C2/3 Cbl-b) prevented the downregulation of the EGFRvIII by Cbl-b (Figure 3b, lane 5). Finally, a RING finger mutant of Cbl-b (C373A) that has been shown to lack E3 activity (Ettenberg et al, 2001) was unable to downregulate the EGFRvIII (Figure 3b, lane 6). Quantification of the downregulation of the EGFRvIII by the various constructs of Cbl-b revealed that N1/2 and WT Cbl-b downregulate the EGFRvIII to a similar extent, that the overexpression of C2/3 Cbl-b did not affect EGFRvIII levels, and that the RING finger mutant of Cbl-b tended to increase the amount of the EGFRvIII protein ( Figure 3c).…”
Section: Requirements For Cbl-b-mediated Downregulation Of the Egfrviiimentioning
confidence: 99%
See 2 more Smart Citations